(3QhVI GdCfS hfRgI GdfaSs - (3GdQfOj , UGdM Hf jRjO Hf UGdM Hf ehSi Hf CHj GdbGSe Hf Ydj Hf TQja GdfaRj, CHh GdWjH CHh GdHbGA,J (B684 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdChd bHd hLhO GdChGFd GdBNQ HYO KHhJ GdOdGFd s
(3BNQgG (B:s
(3jfJgi CKfGA GdHGH GdJGSY ai GdaJhM HGdcdGe Ydi aJM eUQ hGdGScfOQjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B198s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs